The traditional courtyard house of Lahore: an analysis with respect to Deep Beauty and sustainability - Qureshi, Rabia Ahmed (Kansas State University, 2015)
Sustainability is essential for survival on this planet but only focusing on the green aspects is not a comprehensive solution. The idea of Deep Beauty provides a more thorough and complete framework that is the answer to the sustainability problem of today. This framework is comprised of three levels: functional, typological and archetypal. These three levels combined, look at a building in terms of its functionality, its relevance to its region and the universal beauty that it must possess to exist long term. The union of aesthetics with function is what can save the planet. For this research, the focus of study is the traditional residential architecture of the city of Lahore, Pakistan, a city with a rich cultural background. Throughout history, Lahore has seen many transformations with respect to its architecture. Its architectural history can be traced back to the Indus Valley Civilization in the 3rd millennium BC, to a predominance of Buddhism, to a prevalence of Hinduism transformed further by the advent of Islam, the arrival of the British and the founding of the independent state of Pakistan. Currently, the housing trends are continuing to become more and more westernized in a pattern that is not fit for the region because of their inability to provide comfortable living environments and life-enriching spaces. In order to provide better housing solutions for the future, it is important that we look back at examples that have passed the test of time. This report discusses the present day and traditional housing trends of Lahore. With the purpose of improving the current residential designs, an analysis of a traditional house of Lahore has been performed to learn how it meets the criteria of Deep Beauty and sustainability. The results from this analysis provide design strategies that can be incorporated into present day houses to achieve sustainability. Based on these conclusions, a more sustainable design has been proposed for the modern house.
Keywords: Sustainability; Deep Beauty; Traditional architecture; Lahore; Pakistan; Courtyard house; Architecture (0729)